The Neural Representation of Relational- and Collective-Self: Two Forms of Collectivism - Zheng, Yingcan; Xiao, Zilun; Wei, Luqing; Chen, Hong (Frontiers in Psychology, 2018)
The collectivism can be divided into two forms: relational collectivism and group collectivism. According to the cognitive representation of self, relational collectivism emphasizes the relational-self and group collectivism privileges the collective-self. However, it remains uncertain whether there is a difference between relational-self and collective-self under Chinese collectivism cultural. To address the above issue, the present study examined the neural representation of relational-self and collective-self during trait judgment tasks using fMRI. The results showed that relational-self-reference compared with collective-self-reference generated stronger MPFC activity, indicating relational-self was more closeness and important in the self-concept than collective-self under East Asian cultural background. Relational-self and collective-self are unequally represented in the MPFC, providing direct neural evidence that the collectivism in China can be divided into relational collectivism and group collectivism.